RANCANGAN SISTEM PEMANTAUAN PROSES BIMBINGAN TUGAS AKHIR BERBASIS WEB PADA ITB SWADHARMA - Adi Sopian; Septiana Ningtyas; Serli Aprilia (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
Final Project is a scientific paper on the research that discusses a problem in a particular field of science by using applicable scientific rules so that students can compose and write according to the field of science in understanding, analyzing, and explaining problems and providing solutions that are under the field of science. Likewise, the Swadharma Institute of Technology and Business requires every student to prepare a final project as one of the graduation requirements in obtaining a bachelor's degree. However, based on the analysis using the PIECES method, there were several obstacles encountered in the preparation of this final project, especially during the guidance process, the lecturer had difficulty monitoring the progress of the student guidance final project, due to incomplete files and miss communication between lecturers and students so that the problems in work on the final task cannot be solved immediately. In addition, the Dean finds it difficult to monitor the guidance process between students and lecturers. So it is necessary to have an application that can facilitate the guidance process and monitor activities in the guidance of students' final assignments